THE EFFECTIVENESS OF ONLINE KAJIAN AL-ISLAM AND KEMUHAMMADIYAHAN ASSESSMENT IN THE TIME OF COVID-19 UNIVERSITY OF MUHAMMADIYAH SUMATERA UTARA - Nur Rahmah Amini; Robie Fanreza (Proceeding International Seminar of Islamic Studies, 2021)
The purpose of this study is to obtain information about the effectiveness of the process of implementing an online-based intensive study of Al-Islam and Muhammadiyah during the Covid-19 pandemic. This research uses a qualitative exploratory method with an inductive approach. The researcher deliberately chose 5 people as respondents consisting of 2 lecturers, 1 Co-Instructor, and 2 Students. For the confidentiality of the respondents to be guaranteed, the researchers gave the names of the respondents R1, R2, R3, R4, and R5. Structured interviews were conducted with questions that were compiled and linked and developed with related literature. The results of this study. First, more and more assignments were given to students without explanation. Second, the implementation requires a lot of internet strength, good signal, and good devices. Third, it has not been effective so that the results obtained are not optimal.  Keywords  : Effectiveness, Intensive Studies, Al-Islam and Kemuhammadiyahan